Philosophy of Qur’ānic Weltanschauung in the Light of Different Exegetical Modes: A Discourse of Traditional-cum-Modern Scholarship - Ashfaq, Muhammad; Al Azhari, Manzoor Ahmad (Journal of Islamic and Religious Studies, 2020)
This paper aims to highlight the role of different exegetical approaches considering traditional to that of modern scholarship to comprehend possible dimensions of Qur’ānic worldview regarding a particular topic. This discussion has been demarcated generally into four major phases succinctly with further minor segments where scholars’ elaborations are also important elements expressing their own opinions and vantage points. For example, proportionality and coherence among various Qur’ānic subjects, contextual framework in addition to the involvement of thematic exegetical methodology, etc. where each dimension contributes well up to the possible extent. Employing the analytical method, we may examine the question of Qur’ānic Worldview to judge the text to contextual domain considering traditional vis-à-vis modern scholarship. Hence, this paper finds that in contemporary context together with epistemological concern, the mutual nexus between traditional-cum-modern scholarship supplements each other concerning different exegetical modes concerning cultural fluctuations depending upon the scholar’s capability of inference and insight. All these factors revolve around the various modes integrating the whole concept intermingling number of facets collectively that may project the possible Whole Part Relation Paradigm (WPRP) with a homogeneous view. It leads one to know, highlight, and demonstrates the Qur’ānic weltanschauung.